NATIONALITY COMMUNITY SERVICE PROGRAM THROUGH STRENGTHENING NATIONAL VALUES TO MAINTAIN THE INTEGRITY OF INDONESIA BORDER AREAS - Pramulya, Muhammad; Ramadhan, Iwan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The Nationality Community Service Program XI in 2023 (KKN Kebangsaan XI Tahun 2023) embodies the higher education Tri Dharma by collaborating with students from diverse Indonesian universities and local communities. Focused on villages in Bengkayang and Sambas Regencies, bordering Malaysia to the north, the program addresses local challenges and potentials. KKN's stages involve problem identification, data collection, program development, and evaluation, facilitated by students, government, and non-governmental entities. Evaluation methods include rubrics, focus group discussions, and exams. Noteworthy outcomes include successful natural resource management, sustainable human resources development in education, health, and economy, fostering robust community-university-government networks. The program fosters unity among universities nationwide, bridging geographical gaps for a sustainable and united KKN initiative, contributing to holistic village development and reinforcing national values.